2016
DOI: 10.1007/s00018-016-2308-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic roles in the malignant transformation of gastric mucosal cells

Abstract: Gastric carcinogenesis occurs when gastric epithelial cells transition through the initial, immortal, premalignant, and malignant stages of transformation. Epigenetic regulations contribute to this multistep process. Due to the critical role of epigenetic modifications , these changes are highly likely to be of clinical use in the future as new biomarkers and therapeutic targets for the early detection and treatment of cancers. Here, we summarize the recent findings on how epigenetic modifications, including D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…Promoter hypermethylation of several tumor suppressor genes has been correlated with gastric cancer susceptibility [ 17 ]. The literature reports many genes significantly hypermethylated in cancer tissue compared with normal tissue of GC subjects [ 18 20 ], but relatively few studies have reported DNA methylation markers for early detection [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promoter hypermethylation of several tumor suppressor genes has been correlated with gastric cancer susceptibility [ 17 ]. The literature reports many genes significantly hypermethylated in cancer tissue compared with normal tissue of GC subjects [ 18 20 ], but relatively few studies have reported DNA methylation markers for early detection [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori infection has been correlated with the progressive accumulation of epigenetic alterations in gastric mucosa [ 17 ]. Promoter hypermethylation in specific tumor suppressor genes has been associated with H. pylori infection in the multistep carcinogenetic process by several groups [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic alterations play a pivotal role in the inactivation of tumor suppressor genes and activation of oncogenes in a wide spectrum of tumors including CRC. Alteration of the chromatin status is known to be an early event during the malignant transformation of colonic epithelial cells [ 41 ]. Notably, MLL2 and MLL3 are methyl-transferases that methylate the Lys-4 position of histone H3 and thus represent key transcriptional regulators that are essential for cell differentiation, embryonic development, cell fate transition [ 42 ] metabolism [ 43 ] and tumor suppression [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the early phases of oxyntic gastritis caused by H. pylori, gastric acid secretion may be only moderately reduced and H. pylori eradication even in patients with some degree of atrophy can augment acid secretion (Tie et al, 2016). In patients with pangastritis and oxyntic atrophy, H. pylori may not be detectable.…”
Section: H Pylori and Hypoacidity/ Anaciditymentioning
confidence: 99%